Association between the presence of Helicobacter pylori and the development of de novo anemia in adults undergoing sleeve gastrectomy - Carrillo-Levin, Tammy S. (2024)
Background: Sleeve gastrectomy has gained prominence in obesity treatment, yet it is not without complications, such as the development of anemia in the medium term. Given the high prevalence of Helicobacter pylori infection in Peru, it is imperative to explore its potential association with this postoperative complication. Objective: To evaluate the association between the presence of Helicobacter pylori and the development of anemia 12 months after sleeve gastrectomy. Methods: A retrospective cohort study was carried out based on an analysis of secondary data from a private clinic in Lima, Peru, which included two groups of people over 18 years of age who had undergone sleeve gastrectomy between 2010 and 2020. We considered the subjects who had the previous diagnosis of Helicobacter pylori as well as those who did not have the infection, according to the detection of the bacteria by endoscopy before surgery. Results: A total 313 individuals were analyzed, and it was found that the prevalence of Helicobacter pylori was 46.0% and the incidence of anemia 12 months after sleeve gastrectomy was 18.2%. The presence of Helicobacter pylori increased the risk of de novo anemia (Relative Risk = 1.56; 95% confidence intervals: 1.02–2.41; p = 0.043). When stratifying by sex, the association was maintained only for the male group (Relative Risk = 2.84; 95% confidence intervals: 1.02–7.02; p = 0.047). Conclusions: It was identified that the presence of Helicobacter pylori had a significant association with the development of de novo anemia, mainly in male subjects, 1 year after undergoing sleeve gastrectomy.